Public funding of banks and firms in a time of crisis - Markus Haavio; Antti Ripatti; Tuomas Takalo (Bank of Finland, 2022)
We study public funding of banks and non-financial firms in a time of crisis. We find that bank capitalization is more effective in stabilizing the economy than direct funding to firms, but it also creates larger distortions. We show that the optimal, social-welfare-maximizing, structure of a public funding program depends on its size. Small funding programs should target banks while large programs should be directed at non-financial firms.
urn:nbn:fi:bof-202206271310
Keywords: E44; G21; G28; G38; H12; H81; 330; economic crises; optimal public funding; financial frictions; macro-financial linkages